2016
DOI: 10.1177/0301006616657097
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between Vision and Eye Movements

Abstract: The existence of a central fovea, the small retinal region with high analytical performance, is arguably the most prominent design feature of the primate visual system. This centralization comes along with the corresponding capability to move the eyes to reposition the fovea continuously. Past research on visual perception was mainly concerned with foveal vision while the observers kept their eyes stationary. Research on the role of eye movements in visual perception emphasized their negative aspects, for exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 147 publications
(182 reference statements)
1
69
0
Order By: Relevance
“…Visual rotation has been largely neglected in studies on the visual signals that guide smooth pursuit eye movements, 16,28,29 and on the brain pathways underlying motion processing for pursuit.…”
Section: Discussionmentioning
confidence: 99%
“…Visual rotation has been largely neglected in studies on the visual signals that guide smooth pursuit eye movements, 16,28,29 and on the brain pathways underlying motion processing for pursuit.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the well documented saccadic related suppression in visual cortex (for a review see (Gegenfurtner, 2016)), a plethora of studies have shown in both humans and animals that selfproduced motor activity (e.g. button-pressing, vocalizing, walking, etc.)…”
Section: Motor Related Suppression Of Sensory Corticesmentioning
confidence: 99%
“…A potential key flaw with these eye-movement studies is the assumption that visual 122 attention is always aligned directly with the line of sight. A number of studies have suggested that this may not necessarily be the case (e.g., Datta & DeYoe, 2009;Ehinger & Rosenholtz, 124 2016;Gegenfurtner, 2016). For example, in judgements of a basketball scenario, a contingent-125 gaze paradigm suggests that the position of the player with the ball is used as an "anchor point"…”
mentioning
confidence: 99%